2015
DOI: 10.1111/cas.12836
|View full text |Cite
|
Sign up to set email alerts
|

Apelin as a marker for monitoring the tumor vessel normalization window during antiangiogenic therapy

Abstract: Antiangiogenic agents transiently normalize tumor vessel structure and improve vessel function, thereby providing a window of opportunity for enhancing the efficacy of chemotherapy or radiotherapy. Currently, there are no reliable predictors or markers reflecting this vessel normalization window during antiangiogenic therapy. Apelin, the expression of which is regulated by hypoxia, and which has well‐described roles in tumor progression, is an easily measured secreted protein. Here, we show that apelin can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 53 publications
4
42
0
2
Order By: Relevance
“…A clinical perspective for the coapplication of apelin-F13A together with VEGFA/VEGFR2 inhibitors is also suggested because coadministration of apelin-F13A and DC101 synergistically blunted GBM vascularization and diminished the proinvasive sideeffects associated with VEGFA/VEGFR2 inhibition. In addition, the reduced vascularization might be accompanied with vascular normalization that could be supportive for combined chemotherapy (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical perspective for the coapplication of apelin-F13A together with VEGFA/VEGFR2 inhibitors is also suggested because coadministration of apelin-F13A and DC101 synergistically blunted GBM vascularization and diminished the proinvasive sideeffects associated with VEGFA/VEGFR2 inhibition. In addition, the reduced vascularization might be accompanied with vascular normalization that could be supportive for combined chemotherapy (18).…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxic regions, apelin was highly coexpressed with VEGFA (15)(16)(17). In this context, it was suggested that apelin levels indicate improved tumor hypoxia due to vascular normalization upon bevacizumab treatment (18).…”
Section: Introductionmentioning
confidence: 99%
“…Apelin is an endogenous peptide that belongs to the adipokines family and a ligand for the orphan G protein‐coupled receptor (APJ) . In normal conditions, APJ is expressed in the vascular smooth muscle cells, endothelium, and myocardial cells, and plays an important role in regulating blood pressure, cardiac contractility, and angiogenesis …”
Section: Introductionmentioning
confidence: 99%
“…The only gene found in common in the two comparisons was APLN, encoding apelin. Apelin is an endogenous peptide that functions as the ligand of the G protein-coupled receptor APJ, which may be involved in many physiological processes including angiogenesis [56]. Apelin plays a role in regulating the hemodynamics of pregnancy [57].…”
Section: Discussionmentioning
confidence: 99%